2022
DOI: 10.1111/imj.15672
|View full text |Cite
|
Sign up to set email alerts
|

Excess burden of critical illness related to inflammatory bowel disease

Abstract: Background Although inflammatory bowel disease (IBD) is associated with major morbidity and mortality, few studies have evaluated its associated burden of critical illness. Aims To examine the epidemiology and outcome of intensive care unit (ICU) admission among patients with IBD in North Brisbane, Australia. Methods A population‐based cohort design was used. All admissions to ICU serving the Metro North Hospital and Health Service among adult residents during 2017–2019 were included. Data were obtained from I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
(58 reference statements)
1
2
0
Order By: Relevance
“…Taken together, these data show that IBD patients seem not to be overrepresented in their admission rates to the ICU compared to the general population. This is an interesting finding as previous studies have described a higher risk for IBD patients to be admitted to the ICU [5][6][7][8].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Taken together, these data show that IBD patients seem not to be overrepresented in their admission rates to the ICU compared to the general population. This is an interesting finding as previous studies have described a higher risk for IBD patients to be admitted to the ICU [5][6][7][8].…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies have shown that common complications that may require intensive care are caused by fistulas, abscesses, and intestinal obstructions that require surgical intervention and postoperative care, as well as severe systemic symptoms. These symptoms include a loss of intravascular volume and electrolyte derangement caused by severe diarrhea, thromboembolic events, and infections favored by immunosuppressant therapy [5][6][7][8]. Mortality rates of IBD patients admitted to the ICU have been described as ranging from 15 to 19%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation